Cardiac Angiosarcoma-Associated Membranoproliferative Glomerulonephropathy. (18th May 2011) - Shahani, Lokesh; Beckmann, Michael; Vallurupalli, Srikanth
Abstract : Primary cardiac angiosarcoma is a rare cardiac tumor. The initial clinical course is often asymptomatic, and metastatic disease is present in a majority of affected patients at diagnosis. We present a patient who presented with a hemorrhagic pericardial effusion. No malignant cells were evident on cytological examination. He subsequently developed membranoproliferative glomerulonephritis requiring hemodialysis. Metastatic cardiac angiosarcoma was diagnosed 5 months later. To our knowledge, this is the first reported case of paraneoplastic membranoproliferative glomerulopathy associated with cardiac angiosarcoma.